Classification and evaluation of the environment of the professional nursing practice in a teaching hospital - Dilzabeth Margot Imata Yanarico; Alexandre Pazetto Balsanelli; Renata Cristina Gasparino; Elena Bohomol (Universidade de São Paulo, 2020)
Objective: to classify and evaluate the environment of the professional nursing practice in a teaching hospital. Method: a cross-sectional study conducted with 188 nurses from a teaching hospital in the state of São Paulo, SP, Brazil. A questionnaire with sociodemographic and professional data and the Brazilian version of the Practice Environment Scale were used to classify and evaluate the environment of the professional nursing practice. Data was analyzed using Student's t-test, analysis of variance, Mann-Whitney, and Kruskal-Wallis tests with a significance level of 5% (p<0.05). The internal consistency of the instrument was evaluated using Cronbach's alpha. Results: the score's mean for the Brazilian version of the Practice Environment Scale was 2.54, and the participants considered two of the five subscales as unfavorable for the practice, namely: subscale 1, "Nurse Participation in Hospital Affairs" (2.37), and subscale 4, "Staffing and Resource Adequacy" (2.23). Conclusion: the environment of the professional nursing practice has been classified as mixed, being evaluated with favorable conditions for the nursing practice, but the participation and involvement of nurses in hospital matters and the adequacy of resources to provide quality care need improvements.